Indian Ocean humpback dolphin (Sousa plumbea) movement patterns along the South African coast. Issue 1 (17th November 2017) - Vermeulen, Els; Bouveroux, Thibaut; Plön, Stephanie; Atkins, Shanan; Chivell, Wilfred; Cockcroft, Vic; Conry, Danielle; Gennari, Enrico; Hörbst, Sandra; James, Bridget S.; Kirkman, Stephen; Penry, Gwenith; et al.
Abstract: The Indian Ocean humpback dolphin was recently uplisted to 'Endangered' in the recent South African National Red List assessment. Abundance estimates are available from a number of localized study sites, but knowledge of movement patterns and population linkage between these sites is poor. A national research collaboration, the SouSA project, was established in 2016 to address this key knowledge gap. Twenty identification catalogues collected between 2000 and 2016 in 13 different locations were collated and compared. Photographs of 526 humpback dolphins (all catalogues and photos) were reduced to 337 individuals from 12 locations after data selection. Of these, 90 matches were found for 61 individuals over multiple sites, resulting in 247 uniquely, well‐marked humpback dolphins identified in South Africa. Movements were observed along most of the coastline studied. Ranging distances had a median value of 120 km and varied from 30 km up to 500 km. Long‐term site fidelity was also evident in the data. Dolphins ranging along the south coast of South Africa seem to form one single population at the western end of the species' global range. Current available photo‐identification data suggested national abundance may be well below previous estimates of 1000 individuals, with numbers possibly closer to 500. Bearing in mind the poor conservation status of the species in the country, the development of a national Biodiversity Management Plan aimed at ensuring the long‐term survival of the species in South Africa is strongly recommended. At the same time, increased research efforts are essential, particularly to allow for an in‐depth assessment of population numbers and drivers of changes therein. The present study clearly indicates the importance of scientific collaboration when investigating highly mobile and endangered species.